2021
DOI: 10.3390/en14041065
|View full text |Cite
|
Sign up to set email alerts
|

Clarifications on the Behavior of Alternative Gases to SF6 in Divergent Electric Field Distributions under AC Voltage

Abstract: Negative and positive partial discharge inception voltages and breakdown measurements are reported in a needle-plane electrode system as a function of pressure under AC voltage for natural gases (N2, CO2, and O2/CO2), pure Novec TM gases (C4F7N and C5F10O) and Novec TM in different natural gas admixtures. For compressed 4% C4F7N–96% CO2 and 6% C5F10O–12% O2–82% CO2 gas mixtures, the positive-streamer mode is identified as the breakdown mechanism. Breakdown and negative partial discharge inception voltages of 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…39 It was also found that the breakdown voltage for mixtures of 20% C 4 F 7 N and 80% CO 2 follows a nonlinear pattern as pressure increases. 40 When it comes to general-purpose chemical trace analysis, GC has been the default laboratory technique for separating and analyzing mixtures. Components are separated by moving through a chromatography column before being analyzed by a detector.…”
Section: ■ Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…39 It was also found that the breakdown voltage for mixtures of 20% C 4 F 7 N and 80% CO 2 follows a nonlinear pattern as pressure increases. 40 When it comes to general-purpose chemical trace analysis, GC has been the default laboratory technique for separating and analyzing mixtures. Components are separated by moving through a chromatography column before being analyzed by a detector.…”
Section: ■ Backgroundmentioning
confidence: 99%
“…These parameters also affect the insulating ability of C 4 F 7 N. For example, as the distance between the arc contacts in a circuit breaker increases, the insulating efficiency of the gas is improved . It was also found that the breakdown voltage for mixtures of 20% C 4 F 7 N and 80% CO 2 follows a nonlinear pattern as pressure increases …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Swarm parameters such as ionization and attachment coefficients have been experimentally measured to determine the reduced critical electric field and to estimate the dielectric strength of C 4 F 7 N mixtures [15][16][17][18][19][20]. Furthermore, their breakdown characteristics and dielectric properties have been extensively investigated through experimental measurements [21][22][23][24][25][26][27][28][29][30] as well as theoretical calculations [31][32][33]. C 4 F 7 N-CO 2 mixtures with approximately 10%-20% C 4 F 7 N have been found to achieve a comparable dielectric strength to SF 6 under varying conditions.…”
Section: Streamer Discharges In C 4 F 7 N-co 2 Mixturesmentioning
confidence: 99%